Determination of Risk Factors Associated with the Development of Cervical Cancer in Mirpur, AJK - Ijaz Ali, Muhammad Usman Anjum, Raheel Afridi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cervical cancer is an important public health issue. Numerous factors are associated with the development of cervical cancer. Aim: To understand various contributory and risk factors associated with the development of cervical cancer in our area. Study design: Descriptive cross-sectional study. Duration and place of study: Mohi-ud-Din Islamic Medical College, Mirpur AJK from October 2021 to March 2022. Methods: Volunteering women were included in the study. A pre-tested questionnaire was used to collect data. The proforma included demographic and epidemiological information as well as about the various risk factors which were associated with the development of cervical carcinoma. A detailed medical history was taken and special emphasis was placed on the gynecological history including obstetrical and menstrual history as well as sexual and reproductive history together with contraception usage. Results: There were 753 study participants and their mean age was 56.80±10.51years. The mean age of first sexual intercourse was 17±2.80 years and the average number of pregnancies was two. About 14.61% of our study population was smoker. Hormonal contraception was practiced by 64.01% while 11.29% preferred intra-uterine contraceptive device as a mode of contraception. The prevalence of sexually transmitted diseases was 10.49% and out of these diseases, condylomatosis accounted for 05.84% of cases while syphilis and human immunodeficiency virus were responsible for 04.78% of cases collectively. Conclusion: There are various risk factors associated with the development of cervical cancer. Most important of them are younger age at marriage or sexual activity, use and duration of contraception usage and smoking. There is a need to arrange awareness campaigns among masses to raise awareness about the risk factors and also about the benefits of early screening so as to prevent the development of cervical cancer. Keywords: Human Papilloma Virus, Risk Factors, Cervical Cancer, Women, Contraception, Screening